Call for Emergency Action to Limit Global Temperature Increases, Restore Biodiversity, and Protect Health: Wealthy Nations Must do Much More, Much Faster - Lukoye Atwoli; Abdullah H. Baqui; Thomas Benfield; Raffaella Bosurgi; Fiona Godlee; Stephen Hancocks; Richard Horton; Laurie Laybourn-Langton; Carlos Monteiro; Ian Norman; Kirsten Patrick; Nigel Praities; et al. (Ubiquity Press, 2021)
Joint editorial calling for emergency action to limit global temperature increases, restore biodiversity, and protect health.